The determining of psychological well-being levels of athletes playing in university teams Üniversite takımlarında oynayan sporcuların psikolojik iyi oluş düzeylerinin belirlenmesi - Aydın, Elif; Birol, Sefa Şahan; Temel, Veysel (Journal of Human Sciences, 2018)
The aim of this project is to determine the psychological well-being of the students who play in Karamanoğlu Mehmetbey University teams in the framework of sub-dimensions according to different variables. The universe of study consist of 214 athletes active in team sports at Karamanoğlu Mehmetbey University in 2017-2018 academic year while the research group consists of 100 athletes. The data were collected using the personal information form prepared by the researcher and the Psychological Well-Being Scale. In the analysis of the data; frequency, Anova, Kruskal Wallis-H significance test and T-Test. As a result of the findings, according to sub-dimensions of psychological well-being; the difference in autonomy sub-dimension in terms of gender change was found statistically significant. There was no significant difference in age, department, family monthly income situation variables. As a result, participants' psychological well-being scores were found to be above average. Extended English summary is in the end of Full Text PDF (TURKISH) file. Özet Bu çalışmanın amacı, Karamanoğlu Mehmetbey Üniversitesinde, üniversite takımlarında oynayan öğrencilerin psikolojik iyi oluş düzeylerini farklı değişkenlere göre tespit edebilmektir. Yapılan çalışmanın evrenini 2017-2018 akademik yılında Karamanoğlu Mehmetbey Üniversitesi’nin takım sporlarında aktif görev alan 214 sporcu oluştururken, örneklemi 100 sporcu oluşturmaktadır. Veriler araştırmacı tarafından hazırlanan kişisel bilgi formu ve Psikolojik İyi Olma Ölçeği ile toplanmıştır. Verilerin analizinde; frekans, Anova, Kruskal Wallis-H anlamlılık testi ve T-Testi uygulanmıştır. Elde edilen bulgular neticesinde, psikolojik iyi oluşun alt boyutlarına göre; cinsiyet değişkeni açısından özerklik alt boyutunda fark istatistiksel olarak anlamlı bulunurken; yaş, bölüm, aile aylık gelir durumu değişkenlerinde anlamlı bir farklılığa rastlanmamıştır. Sonuç olarak, katılımcıların psikolojik iyi oluş puanlarının ortalamanın üstünde olduğu tespit edilmiştir.